Polymer materials for high‐performance triboelectric nanogenerators - Chen, Aihua; Zhang, Chen; Zhu, Guang; Wang, Zhong Lin (John Wiley and Sons Inc., 2020)
As an emerging branch of energy conversion technologies, the triboelectric nanogenerator (TENG) pioneers a brand‐new path to effectively harness varieties of mechanical energies for the purpose of powering and/or sensing. Since its invention in 2012, the TENG has experienced a booming and revolutionary development in every respect, ranging from materials synthesis and modification, architecture design to performance optimization, power management, and application exploration. In comparison to the organic solar cell and organic light‐emitting diodes, TENG is a unique technique that opens the venue of using polymer materials (PMs) for harvesting mechanical energy. So far, by virtue of superior charge transfer and capturing capabilities during friction, various kinds of PMs have been developed and used as triboelectric materials in order to achieve high‐performance TENGs. Here, this work focuses on the utilization and development of PMs for the TENGs technology and first gives a summary of main PMs that are frequently adopted in currently reported energy‐harvesting TENGs. Second, several kinds of PMs used lately in a few novel TENGs for special or specific energy‐harvesting circumstances are introduced and highlighted. Finally, the perspectives on and challenges in developing high‐performance PMs toward TENGs technology are conceived and expected to be instructive to future research.